Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Volume Pembelian Cabe Merah di Pasar Sulak Kecamatan Kayu Aro Kabupaten Kerinci - Asmaida Asmaida; Iqwan Aldo Putra (Universitas Batangahari Jambi, 2023)
The research was carried out at the Sulak Market, Kayu Aro District, Kerinci Regency, with the aim of describing consumer decisions in purchasing red chilies at the Sulak Market, Kayu Aro District, Kerinci Regency and analyzing the factors that influence consumers in purchasing volume of red chilies. Sampling in this study was using accidental sampling technique with 35 respondents. The data collected includes primary data and secondary data with cross section data types. The results showed that consumer behavior in Kayu Aro District, namely that the average consumer has a spicy taste, therefore consumers always buy red chilies and make preparations because consumers feel happy if red chilies are always available at home. In addition, consumers also think that they are less appetizing if they eat without chili sauce, which is a processed product from red chilies. From the results of this study, it was obtained that consumer behavior towards decisions in purchasing red chilies at Sulak Market, Kayu Aro District, seen from the variable price, number of family dependents, and consumer tastes, they decided to keep buying red chilies. Consumers will feel satisfied if they consume red chili and if it is always available. The results of statistical tests using multiple linear regression, simultaneously (the price of red chilies, the price of substitute goods or cayenne pepper, the number of family members and consumer tastes) have a real influence on consumer decisions in purchasing red chilies at Sulak Market, Kayu Aro District, Kerinci Regency. Partially test there are three factors that significantly affect consumer decisions in buying red chili, namely the price of red chili, the number of family members and consumer tastes while the price of cayenne pepper has no effect. The coefficient of determination for these three factors is 75.2%, which means that these three factors as independent variables are able to explain consumer decisions in purchasing red chilies as dependent variables and around 24.8% cannot be explained by the model but explained by other factors. those models.